Existence and stability analysis for fractional impulsive caputo difference-sum equations with periodic boundary condition - Rujira Ouncharoen (2020)
© 2020 by the authors. In this paper, by using the Banach contraction principle and the Schauder's fixed point theorem, we investigate existence results for a fractional impulsive sum-difference equations with periodic boundary conditions. Moreover, we also establish different kinds of Ulam stability for this problem. An example is also constructed to demonstrate the importance of these results.